A single-institution study of concordance of pathological diagnoses for interstitial lung diseases between pre-transplantation surgical lung biopsies and lung explants. - Panchabhai, Tanmay S.; Arrossi, Andrea Valeria; Farver, Carol F.; Highland, Kristin B.; Culver, Daniel A.; Budev, Marie M.; Bandyopadhyay, Debabrata (BMC Pulmonary Medicine, 2019)
Background: By comparing diagnoses made by pre-transplant surgical lung biopsy (SLB) and the final pathologic diagnosis of the explanted pathology (EP), we aimed to study the factors that could impact pathologic diagnoses in patients with interstitial lung disease (ILD).Methods: We retrospectively reviewed the lung transplant database at Cleveland Clinic [01/01/2006-12/31/2013] to include all lung transplant recipients with a prior diagnosis of ILD. Two pulmonary pathologists independently reviewed each SLB and lung explant. The diagnoses were labeled as concordant (same diagnosis on SLB and explant) or discordant (diagnosis on SLB and explant were different) by consensus.Results: Of 389 patients transplanted for ILD, 217 had an SLB before transplant. Pathological diagnoses were concordant in 190 patients (87.6%) [165 UIP (86.8%), 13 NSIP (6.8%), 8 CHP (4.2%) and 4 other diagnoses (2.1%). In 27 cases (12.4%), the diagnosis on SLB differed from EP. 8/27 were diagnosed with UIP on SLB and of these, 5 were re-classified as NSIP. 14/19 (73.7%) patients with a SLB diagnosis "other than UIP" were re-categorized as UIP based on explant. Discordant cases had a greater time between SLB and EP than concordant cases (1553 days vs 1248 days).Conclusions: The pathologic diagnosis of ILD by SLB prior to lung transplant is accurate in most patients, but may be misleading in a small subset of patients. The majority of discordant cases that were reclassified as UIP could be due to a sampling error, or perhaps, an increased time from the date of the SLB to transplant. Future studies examining how multidisciplinary consensus diagnosis affects this discordance are necessary.